Batang ama a study on the impact of family communication patterns and power within the family to the pregnancy resolution of adolescents fathers - Tolosa, Gracely V. (College of Arts and Letters, University of the Philippines Diliman, 2019)
This qualitative study aims to find out the impact of family communication patterns and power within the family to the pregnancy resolution of adolescent fathers. Specifically,it seeks to describe the following 1) the family communication patterns of the adolescent fathers' family, 2) the power relations within the families of the adolescent fathers, 3) and the impact of the family communication patterns of the adolescent fathers' families and power relations within the family to the pregnancy resolution of the adolescent fathers. The current study used Koerner and Fitzpatrick's (2002) Family Communication Patterns Theory as basis for its conceptual framework. Data gathering procedure involved one-on-one in-depth interviews with five male teenagers,aged 13-22 years old, who have gotten their partners pregnant when they were teenagers. Based on the findings, there were two respondents that displayed as consensual family communication pattern , another two that displayed a laissez-fair family communication pattern, and only one displayed a protective family communication pattern. Teenage pregnancy setting had an impact to the power relations within families of the respondents. There was a strong power relation between the male teenagers and their parents in families that highly resonated a consensual and protective family type, while there was a loose power relation between male teenager and his parents for the family that showed a laissez-fair family type. Given all these, the family communication patterns had an impact on the pregnancy resolution of the adolescent fathers and the power within the family had no impact. The gender, Filipino family culture, and economic, however were other noticeable factors that had an impact about the pregnancy resolution of the adolescent fathers.